Critical Practice - McQuillan, Martin (The WISH List, 2019)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. What is the relationship between theory and practice in the creative arts today? In Critical Practice, Martin McQuillan offers a critical interrogation of the idea of practice-led research. He goes beyond the recent vocabulary of research management to consider the more interesting question of the emergence of a cultural space in which philosophy, theory, history and practice are becoming indistinguishable. McQuillan considers the work of a number of writers and thinkers who cross the divide between theoretical and creative practice, including Alain Badiou and Terry Eagleton, and the longer tradition of 'theory-writing' that runs through the work of Hélène Cixous, Roland Barthes and Louis Althusser. His aim is to elucidate the contemporary ramifications of a relationship that has been contested throughout the long history of philosophy, from Plato's dialogues to Derrida's 'Envois'.